Status Gizi Dengan Kejadian Anemia Pada Mahasiswi Institut Komunikasi Dan Bisnis LSPR Jakarta - Friska Junita; Puri Kresna Wati; Rona Ulfah (Jurnal Ilmiah Kesehatan Sandi Husada, 2023)
Female students who are classified as teenagers have a high risk of anaemia, especially iron nutritional anaemia. College students generally have unhealthy eating habits. Based on Riskesdas data, the proportion of anaemia in women (27.2%) is higher than in men (20.3%). The proportion of anaemia in the age group of 15–24 years is 32%. Based on Riskesdas data, the prevalence of anaemia in adolescents is 32%, meaning that 3–4 out of 10 adolescents suffer from anaemia. Nationally, the prevalence of wasting (according to BMI/U) in children aged 5–12 years is 11.2%, consisting of 4.0% being skinny and 7.2% being underweight (Ministry of Health, 2020). LSPR Jakarta Institute of Communication and Business students found many cases suspected of having anaemia. This is evidenced by the symptoms of female students coming to the clinic for health consultations. The design used in this study is quantitative, using the cross-sectional approach method. The sample in this study was 75 female students of the LSPR Institute of Communication and Business in 2022, using a random sampling technique. The analysis used in this study is the Chi-square test. The results showed that the nutritional status of underweight female students was 45 (60%), while the incidence of anaemia was 43 (57.3%). The results of the chi-square test obtained a p-value of 0.000 <0.05, meaning that there was a relationship between nutritional status and the incidence of anaemia among female students at the Communication Institute and LSPR business in 2022. Advice for LSPR. Health workers should be able to provide health promotion related to nutritional status and anaemia to female students so that they can change healthy living behaviours.